3x*(2x+5)-(x+3)*(3x-1)=1

Simple and best practice solution for 3x*(2x+5)-(x+3)*(3x-1)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x*(2x+5)-(x+3)*(3x-1)=1 equation:


Simplifying
3x(2x + 5) + -1(x + 3)(3x + -1) = 1

Reorder the terms:
3x(5 + 2x) + -1(x + 3)(3x + -1) = 1
(5 * 3x + 2x * 3x) + -1(x + 3)(3x + -1) = 1
(15x + 6x2) + -1(x + 3)(3x + -1) = 1

Reorder the terms:
15x + 6x2 + -1(3 + x)(3x + -1) = 1

Reorder the terms:
15x + 6x2 + -1(3 + x)(-1 + 3x) = 1

Multiply (3 + x) * (-1 + 3x)
15x + 6x2 + -1(3(-1 + 3x) + x(-1 + 3x)) = 1
15x + 6x2 + -1((-1 * 3 + 3x * 3) + x(-1 + 3x)) = 1
15x + 6x2 + -1((-3 + 9x) + x(-1 + 3x)) = 1
15x + 6x2 + -1(-3 + 9x + (-1 * x + 3x * x)) = 1
15x + 6x2 + -1(-3 + 9x + (-1x + 3x2)) = 1

Combine like terms: 9x + -1x = 8x
15x + 6x2 + -1(-3 + 8x + 3x2) = 1
15x + 6x2 + (-3 * -1 + 8x * -1 + 3x2 * -1) = 1
15x + 6x2 + (3 + -8x + -3x2) = 1

Reorder the terms:
3 + 15x + -8x + 6x2 + -3x2 = 1

Combine like terms: 15x + -8x = 7x
3 + 7x + 6x2 + -3x2 = 1

Combine like terms: 6x2 + -3x2 = 3x2
3 + 7x + 3x2 = 1

Solving
3 + 7x + 3x2 = 1

Solving for variable 'x'.

Reorder the terms:
3 + -1 + 7x + 3x2 = 1 + -1

Combine like terms: 3 + -1 = 2
2 + 7x + 3x2 = 1 + -1

Combine like terms: 1 + -1 = 0
2 + 7x + 3x2 = 0

Factor a trinomial.
(2 + x)(1 + 3x) = 0

Subproblem 1

Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(1 + 3x)' equal to zero and attempt to solve: Simplifying 1 + 3x = 0 Solving 1 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 0 + -1 3x = 0 + -1 Combine like terms: 0 + -1 = -1 3x = -1 Divide each side by '3'. x = -0.3333333333 Simplifying x = -0.3333333333

Solution

x = {-2, -0.3333333333}

See similar equations:

| 11z^2+54=36 | | 10x+80=100 | | (3*4)n-9n=39 | | 5.23-(-9.1)= | | X^2=8x-20 | | r^2+4r+6r+24= | | -9.82+(-15.7)= | | m-3=40 | | 12+5=6+23 | | 2x+x+3+x=180 | | X*(x-7)=8 | | 5(b-6)= | | 74+114= | | 2*37= | | 3y-11=3(2y-1)-2y | | -2b+5b-7b= | | 63*63= | | (n-2)*4=24 | | -3b+6b= | | 2b-5b+6b= | | 4x=102 | | 6x+49=8x-5 | | -6r-6r= | | -10=1-3p-5 | | -2j+7j= | | -10x+x^2=-25 | | 3(3x+1)=7(x+1) | | 16=-2x-2x | | 3(3x+1)=7(x+3) | | 2x+x+(x+5)=85 | | 29v^2-18v^2=44 | | 3x^3+9x^2+3x-3=0 |

Equations solver categories